Early-Onset Alzheimer’s Disease: What Is Missing in Research? - Temitope Ayodele; Ekaterina Rogaeva; Jiji T. Kurup; Gary W. Beecham; Christiane Reitz (2021)
Early-onset Alzheimer's disease (EOAD), defined as Alzheimer's disease (AD) occurring before age 65, is significantly less well studied than the late-onset form (LOAD) despite EOAD often presenting with a more aggressive disease progression. The aim of this review is to summarize the current understanding of the etiology of EOAD, their translation into clinical practice, and to suggest steps to be taken to move our understanding forward.